Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3389/fimmu.2023.1123913
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the common genetic landscape of COVID-19 and male infertility

Abstract: BackgroundCOVID-19 has spread widely across continents since 2019, causing serious damage to human health. Accumulative research uncovered that SARS-CoV-2 poses a great threat to male fertility, and male infertility (MI) is a common comorbidity for the COVID-19 pandemic. The aim of the study was to explore the cross-talk molecular mechanisms between COVID-19 and MI.Materials and methodsA total of four transcriptome data regarding COVID-19 and MI were downloaded from the Gene Expression Omnibus (GEO) repository… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…The GSE160749 dataset from the GEO database is a recently updated sperm transcriptome profile of samples from infertile men, and it includes five asthenozoospermia files, seven asthenoteratozoospermia files, six infertile files and six fertile control sample files. A PubMed search revealed that a limited number of relevant studies have contributed to this dataset ( 22 ). Therefore, in the present study, five asthenozoospermia files and six fertile control sample files were selected as a dataset to analyze novel key genes in asthenozoospermia.…”
Section: Discussionmentioning
confidence: 99%
“…The GSE160749 dataset from the GEO database is a recently updated sperm transcriptome profile of samples from infertile men, and it includes five asthenozoospermia files, seven asthenoteratozoospermia files, six infertile files and six fertile control sample files. A PubMed search revealed that a limited number of relevant studies have contributed to this dataset ( 22 ). Therefore, in the present study, five asthenozoospermia files and six fertile control sample files were selected as a dataset to analyze novel key genes in asthenozoospermia.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent article, the authors showed that intraperitoneal administration of biotin to mice resulted in an increase in testosterone levels in serum and testes; as reported, this effect might be mediated by an increase in adenosine 3′,5′-cyclic monophosphate (cAMP) and subsequent activation of protein kinase A [ 185 ]. In another recent article, it was implied that biotin, among other pharmacologically active compounds (ascorbic acid, biotin, caffeine, and L-cysteine) may target COVID-19-related differentially expressed genes and affect COVID-19-associated male infertility [ 186 ]. According to a recent study, secretion of positive emotional tears was correlated with biotin and caffeine metabolism, which might be exploited in the identification of fake tears [ 187 ].…”
Section: Further Perspectivesmentioning
confidence: 99%